Intervención de enfermería en un paciente con ulceras por decúbito con comorbilidades - Menoscal Ponce , Milena Antonella (2024)
The purpose of this study was to analyze the management of pressure ulcers in a 47-year-old female patient who came to the local second level hospital, going to the emergency area because she presented various signs and symptoms of complexity, with pressure ulcers being one of her major complications. Pressure ulcers (PU) are lesions in the skin and underlying tissue caused by prolonged pressure in the sacral area belonging to stage IV. In the approach to these lesions, the nursing interventions developed were to perform a thorough risk assessment of pressure ulcers, identifying predisposing factors such as immobility, humidity, malnutrition and friction, these factors, together with the patient's general health condition, negatively influenced the ability to improve skin integrity within the expected period. Based on this assessment, an individualized care plan was established which included preventive measures such as postural changes every two hours, as well as treatment based on daily dressings and administration of prescribed medications. The expected results in improving the patient's skin integrity were not achieved as expected due to the limited hospitalization time which restricted the ability to carry out prolonged and effective interventions. It is crucial to recognize the importance of a multidisciplinary and continuous approach where the role of nursing is fundamental in the prevention and treatment of pressure ulcers. Coordination between different specialties and the implementation of comprehensive care are essential to effectively address these complications, thus ensuring quality care that promotes better recovery and quality of life.